Burnout Syndrome and nursing care in the Intensive Care Unit in view of the COVID-19 pandemic - Silva, Ana Luiza Gonçalves da (2021)
The objective is to reflect based on a national and international scientific review on the magnitude of Burnout Syndrome in nurses working in the Intensive Care Unit in the context of the Coronavirus 2019 Disease pandemic (COVID-19). This is an integrative literature review, based on a search for complete articles published in the following databases: Latin American and Caribbean Literature in Health Sciences, Online Scientific Electronic Library, Nursing Databases and Medical Literature Analysis and Retrievel System Online, published between 2019 and 2021. The results were included in ten publications in the final study sample. There was a tendency for nurses to progress with Burnout Syndrome during a pandemic, such as COVID-19; at first, the onset or increase of symptoms appears on a daily basis, culminating in a severe state of physical and emotional exhaustion that leads to the emergence and advancement of the syndrome over time. We can say that in relation to the magnitude of Burnout Syndrome in nurses working in the Intensive Care Unit in the context of the COVID-19 pandemic, such superior professionals are higher in Burnout Syndrome when compared to other sectors.